Effects of Reduced Dietary Protein Concentrations with Amino Acid Supplementation on Performance and Carcass Quality in Turkey Toms 14 to 140 Days of Age - Lemme, A.; Frackenpohl, U.; Petri, A.; Meyer, H. (International Journal of Poultry Science, 2004)
An experiment over five grow-out phases was conducted with male B.U.T. Big 6 turkeys from day fourteen to 140. Four dietary treatments differing in protein concentration and amino acid supply were employed. Treatment 1 represented current feeding practice with relatively high protein concentrations of 265 g/kg in phase two (3-5 weeks) feed which then was gradually reduced to 161g/kg in P-VI feed (18-22 weeks). In treatment 2 dietary protein was reduced by ten percent but all essential amino acids were balanced according to the amino acid profile of treatment 1. Diets fed in treatment 3 had also a ten percent reduced protein concentration but only Lys, Met+Cys, Thr, and Trp were balanced in feed formulation resulting in lower Arg, Val, Ile, and Leu concentrations compared to treatments 1 and 2. In treatment 4 crude protein was reduced by 20% but essential amino acids were balanced as in treatment 2. Results suggested that low protein diets with a protein reduction up to ten percent can be fed without adverse effects on animal performance and carcass traits provided the whole range of essential amino acids is balanced. It was concluded that Arg, Val, Ile, and Leu are important for optimum growth and should therefore be considered in diets containing 10% less crude protein. It was further concluded that in low protein diets providing sufficient amounts of essential amino acids the ratio between sum of all essential amino acids should not be higher than 48% of protein.